Politisering av feminism. Jämställdhetsfrågor i Aftonbladets partiledardebatt inför riksdagsvalet 2014 - Domeradzka, Magdalena (Folia Scandinavica Posnaniensia, 2016)
This paper investigates a part of the party leaders’ webb-tv debate staged by the Swedish tabloid Aftonbladet on the 1st of September as a part of the election campaign before the elections to the Riksdag, county councils and municipal assemblies that took place on the 14 September 2014. The debate investigated in this paper deals with gender equality questions. The overall aim of this study is to examine what topics the politicians choose to discuss during the debate and what line of argumentation they use. The method used was ideological discourse analysis coupled with classical rhetoric and eristic. The results of the argumentation analysis are set in a broader framework of gender studies and the Swedish political landscape.